Analisis Kecemasan Matematika dalam E-Learning Mata Kuliah Statistik di Universitas Muhammadiyah Kupang: Analysis of Mathematics Anxiety in E-Learning Statistics Courses at Muhammadiyah University Kupang - Listyotami, Mega Kusuma; Wahyuningsih, Endang (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
Analyzing students' mathematical anxiety in relation to E-learning in statistics courses at Muhammadiyah University Kupang is the aim of this research. This research uses a triangulation design using various data sources such as documents, interview results and observation results. Fifty students from Muhammadiyah University of Kupang were used as research samples. Data collection methods include observation, interviews, mathematical anxiety questionnaires, and E-learning questionnaires. This research uses quantitative and qualitative data analysis methods. Research findings show that E-learning is influenced by mathematical anxiety. There is a correlation of 0.916 between mathematical anxiety and E-learning. Mathematics anxiety has an impact of 83.8% on E-learning.